2006
DOI: 10.1897/05-424r.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of 2,4,2′,4′‐tetrabromodiphenyl ether on the marine alga Skeletonema costatum and the crustacean Daphnia magna

Abstract: Polybrominated diphenyl ethers form a group of highly hydrophobic and persistent chemicals that are detected in various environmental matrices, such as soil, water, sediments, and biota. Although a variety of biological effects have been documented in vertebrates, the effects in invertebrates seem to be largely unknown. The objective of the present study was to determine the toxic effects of 2,4,2',4'-tetrabromodiphenyl ether (BDE 47) on the growth of the marine diatom Skeletonema costatum and on the parthogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Moreover, no effects were also expected to occur in the short term tests at concentrations up to the solubility limit of Octa-BDEs by the analogy with another highly brominated diphenyl ether (decabromodiphenyl ether) [18]. In contrast, Källqvist et al found that BDE-47 caused obvious growth inhibition in the marine diatom Skeletonema costatum , and the no observed effect concentration (NOEC) was 6.6 mg/L [19]. BDE-47 had also been found to depress the growth of four species of marine microalgae and affect the activities of antioxidant enzymes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no effects were also expected to occur in the short term tests at concentrations up to the solubility limit of Octa-BDEs by the analogy with another highly brominated diphenyl ether (decabromodiphenyl ether) [18]. In contrast, Källqvist et al found that BDE-47 caused obvious growth inhibition in the marine diatom Skeletonema costatum , and the no observed effect concentration (NOEC) was 6.6 mg/L [19]. BDE-47 had also been found to depress the growth of four species of marine microalgae and affect the activities of antioxidant enzymes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The culturing of the daphnids were performed according to methods described by Källqvist et al [20].…”
Section: Daphnid Bioaccumulation Testmentioning
confidence: 99%
“…Motility decreased in daphnids at 25, 50 and 100~-LM starting on the third day but no mortality was observed. For the two highest treatments (50 and 100~-LM), the total number of offspring was significantly reduced.Toxicity of BDE47 to D. magna was investigated previously byKallqvist et a/. (2006).…”
mentioning
confidence: 99%